THE STUDY OF SOME PHYSICAL PROPERTIES OF ANDISOLS IN VARIOUS LAND IN JERNIH JAYA VILLAGE, GUNUNG TUJUH DISTRICT, KERINCI REGENCY - Najla Anwar Fuadi; Zurhalena Zurhalena; Agus Kurniawan Mastur (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2024)
ABSTRACT Although Andisols is the best soil type to support plant growth, overuse of Andisols soil type can degrade soil quality. Gunung Tujuh District of Kerinci Regency's Jernih Jaya Village, there is an Andisols land use location. Soil quality is negatively impacted by land management practices, which disregard land sustainability, soil, and water conservation measures. To understand the physical characteristics of Andisolss in various land uses in Jernih Jaya Village, it is vital to examine the effects of different tillages and land uses. The stages were (1) preparation of primary data (taking soil samples) and secondary data (making maps), (2) survey (preliminary survey and main survey), (3) data processing and interpretation of data resulting from analysis of soil samples and surveys. Based on an examination of various physical attributes of Andisols in different land used within Jernih Jaya Village, Gunung Tujuh District, Kerinci Regency, it could be inferred that the physical properties of Andisols were deemed favorable. The results indicated that the area was used for vegetables, plantations, secondary forests, and paddy fields, with slope classes ranging from 0-3%, 3-8%, and 8-15%, sandy loam with a crumb structure in all land used, high water content, moderate to high total pore space, low to medium volume weight, and high organic matter were all present. When compared to other land uses, paddy fields had the highest organic matter content (22.10%), highest moisture content (124.89%), highest total pore space (79.39%), and lowest bulk density (0.57 g/cm3).